Aplicación móvil hibrida utilizando el framework flutter para promocionar los atractivos turísticos del cantón Guano - Ausay Fonseca, Esteban Isaac (2022)
Information and communication technologies (ICTs) have had a great impact in recent years in the tourism field, so the Municipal Decentralized Autonomous Government of Guano Canton (GAD Guano) considered it relevant to use ICTs for development in the tourism industry. In this context, the main objective of this research was to implement a hybrid mobile application using the flutter framework to promote tourism services in the Guano Canton. For the development of the research project was used the Scrum methodology that is characterized by iterative development to ensure good results in a collaborative manner, an application was obtained with a friendly interface with quick access buttons, to facilitate access to its different categories and obtain information on the different tourist attractions. Once the application was completed and the performance tests were executed, a survey was applied to professionals and users to evaluate the usability of the mobile application, which allowed measuring parameters such as effectiveness, efficiency, and satisfaction, demonstrating that it has a satisfactory level of use. The thesis begins with the presentation of the problem presented by the GAD of Guano regarding the promotion of different tourist attractions, the second chapter presents the theoretical framework conceptualizing important topics for a better understanding of the theme, Chapter three discusses the methodology, which defined the type of research, the methods to be used, the techniques of information collection and the development of the application. As a result, a mobile application drives local and foreign tourists to visit the canton.